INDEPENDENSI HAKIM DALAM SISTEM PERADILAN PAJAK DI INDONESIA - Binsar Sitorus (Yuridika, 2013)
Tax court in Indonesia is part of administrative court that has jurisdiction to hear any tax dispute. It is kind of administrative court as it meets such elements, for example one of the parties of the dispute must be government officer, which is bound to an official act taken within the limits of the official authority. Tax court acts as judicial authority provide tribunals for tax payer or tax insurers to resolve disputes regarding taxation. Therefore it can be used as a means for the citizens as a tax payer or insurer to obtain justice in taxation.